The Effect of Leadership on Employee Performance Through Work Motivation as a Mediating Variable in Employee PT Conisla Karya Indonesia - Putri, Diana Suryami; Fatimah, Nuzulul; Putra, Riyan Sisiawan; Anshori, Mohamad Yusak (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to examine the effect of leadership on employee performance through work motivation as a mediating variable. This study uses quantitative methods with primary data obtained from the distribution of questionnaires to 89 employees of PT Conisla Karya Indonesia, with sampling techniques using purposive sampling determined by researchers with consideration of certain characteristics or characteristics based on employee status and division of each employee. Where the results of the questionnaire obtained are processed using Structural Equation Modeling (SEM) PLS 3.0 analysis through outer model analysis, inner model, and hypothesis testing. The results of this study indicate that there is a significant effect of leadership on employee performance, leadership has a significant effect on work motivation, work motivation has a significant effect on employee performance, and work motivation variables can significantly mediate the effect of leadership on performance employees.